A recycled daily-use ceramic product and its production process
By using inorganic antibacterial agents and inorganic modified additives in ceramic products, the problem of poor antibacterial and corrosion resistance of ceramic products is solved, and the efficient antibacterial, corrosion-resistant and wear-resistant properties of ceramic products are achieved, which extends the service life and Ensure health and safety.
Patent Information
- Application Number
- CN202410800812.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-06-20
- Publication Date
- 2025-02-07
- Estimated Expiration
- 2044-06-20
AI Technical Summary
Daily-used ceramic products have poor antibacterial and anticorrosion, are easily contaminated by bacteria, and may cause corrosion, discoloration or cracks after being exposed to acidic or alkaline substances, affecting service life and health and safety.
Inorganic antibacterial agent is used to adsorb copper ions and zinc ions on illite powder, and combine sepiolite fibers with glass flake powder through electrostatic adsorption to prepare inorganic modified additives to improve the antibacterial, corrosion resistance and resistance of ceramic products. Grinding performance.
It effectively improves the antibacterial properties of ceramic products, extends the service life, enhances its resistance to bacteria and corrosion, and ensures health and safety.
Smart Images

Figure CN118754604B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of ceramic products, and in particular to a recycled daily-use ceramic product and a production process thereof. Background Art
[0002] Recycled daily-use ceramic products refer to the use of waste ceramic products that have been processed and then processed into new daily-use ceramic products. They are widely used in various daily-use ceramic products, such as tableware, wine utensils, tea sets, etc. As people's attention to environmental protection and sustainable development continues to increase, recycled daily-use ceramic products have also received more and more attention and recognition. The production and use of these ceramic products can not only save resources and reduce production costs, but also reduce the pollution and damage to the environment caused by discarded ceramic products. Therefore, the application prospects of recycled daily-use ceramic products in the future are very broad.
[0003] Daily-use ceramic products involve all aspects of people's lives. With the improvement of people's living standards, more requirements are put forward for them. Among them, antibacterial is the most common requirement at present. The main purpose is to protect people's health and safety. In daily life, ceramic products such as tableware and water cups are often in contact with people's mouths. If there are bacteria on the surface of ceramic products, these bacteria may enter the human body and cause various diseases. Especially in public places such as restaurants, schools, hospitals, etc., the hygiene of ceramic products is particularly important. If effective antibacterial treatment is not carried out, it is easier to spread diseases. In addition, daily-use ceramic products may be exposed to various acidic or alkaline substances during use. If they are not cleaned properly, their surface may be corroded, discolored or cracked over a long period of time, which will not only affect the service life of ceramic products, but also pose a threat to the health of users.
[0004] At present, one of the most common ways to improve the antibacterial properties of ceramic products is to add antibacterial agents into the glaze or onto the glaze surface to make the ceramic products have antibacterial function. For example, the patent with publication number CN103482957B discloses an antibacterial sanitary ceramic and a preparation method thereof. Nano-silver, nano-silicon oxide, nano-aluminum oxide, nano-titanium and silver nitrate are added into the glaze slurry as a composite antibacterial agent to thereby improve the antibacterial properties of the ceramic products. However, the use of nano-silver as an antibacterial component is costly and not conducive to mass production. In addition, it is easy to oxidize and turn black during the calcination process, affecting the color. Summary of the invention
[0005] The purpose of the present invention is to provide a recycled daily-use ceramic product and a production process thereof, which solves the following technical problems:
[0006] (1) Solved the problem of poor antibacterial properties of daily-use ceramic products;
[0007] (2) Solved the problem of poor corrosion resistance of daily-use ceramic products.
[0008] The purpose of the present invention can be achieved through the following technical solutions:
[0009] A recycled daily-use ceramic product, comprising a ceramic body and a glaze slurry coated on the surface of the ceramic body; the ceramic body is made from waste ceramic products after processing; the glaze slurry comprises the following raw materials by weight: 20 to 30 parts of potassium feldspar, 15 to 25 parts of sodium feldspar, 12 to 18 parts of calcite, 3 to 5 parts of quartz, 1 to 3 parts of kaolin, 5 to 10 parts of silicon dioxide, 5 to 8 parts of aluminum oxide, 4 to 6 parts of calcium oxide, 3 to 5 parts of pigment, 3 to 5 parts of paraffin wax, 5 to 10 parts of inorganic antibacterial agent, 4 to 8 parts of inorganic modified additive, and deionized water; the inorganic antibacterial agent is to adsorb copper ions and zinc ions on illite powder; the inorganic modified additive is to combine sepiolite fiber with glass flake powder through electrostatic adsorption;
[0010] Furthermore, the preparation method of the inorganic antibacterial agent comprises the following steps:
[0011] S1: adding illite powder to a hydrochloric acid solution, stirring at 50-70° C. for 1-3 hours, and then filtering, washing, and vacuum drying to obtain pretreated illite powder;
[0012] S2: dissolving aniline in hydrochloric acid solution, adding pretreated illite powder, ultrasonically dispersing for 1-2 hours, then adding initiator, stirring and mixing evenly, reacting in an ice bath at 0-4°C for 6-10 hours, filtering, washing and drying to obtain modified illite powder;
[0013] S3: Add the modified illite powder into deionized water, ultrasonically disperse for 1 to 2 hours, then add zinc chloride and copper nitrate, continue stirring and mixing for 8 to 10 hours, then filter and dry to obtain an inorganic antibacterial agent.
[0014] Through the above technical scheme, after the illite powder is acid-washed, the hydroxyl groups on the surface of the illite powder are easy to hydrogen bond with the amino groups in the aniline structure, so that the aniline is attached to the illite powder. Then, under the action of the initiator, the aniline undergoes an in-situ polymerization reaction, so that the polyaniline is attached to the illite powder. Then, the positively charged metal ions can interact with the nitrogen atoms on the main chain of the polyaniline, so that the copper ions and zinc ions are adsorbed in the illite powder.
[0015] Furthermore, the preparation method of the inorganic modified additive comprises the following steps:
[0016] Ⅰ: Add sepiolite fiber to ethanol, ultrasonically disperse for 20 to 40 minutes, then add trimethyl [3- (trimethoxysilyl) propyl] ammonium chloride, stir and mix, react at 40 to 60 ° C for 2 to 4 hours, and after the reaction is completed, filter out the solid material, wash and dry to obtain modified sepiolite fiber;
[0017] II: Place the modified sepiolite fiber in deionized water, ultrasonically disperse it for 20 to 40 minutes, add glass flake powder, ultrasonically disperse it for 1 to 2 hours, let it stand for 1 to 2 hours, then filter, vacuum dry, collect the product, grind and sieve it to obtain an inorganic modified additive.
[0018] Through the above technical scheme, the sepiolite fiber is modified using trimethyl [3- (trimethoxysilyl) propyl] ammonium chloride, and the trimethyl [3- (trimethoxysilyl) propyl] ammonium chloride is grafted onto the surface of the sepiolite fiber. Then, the positive charge of the surface-modified quaternary ammonium salt ions in the solution is electrostatically adsorbed with the negatively charged glass flake powder to combine the sepiolite fiber with the glass flake powder to obtain an inorganic modified additive.
[0019] Furthermore, the pigment is any one of cinnabar, red clay or malachite green.
[0020] Furthermore, in step S1, the particle size of the illite powder is 1 to 10 μm.
[0021] Furthermore, in step S2, the concentration of the hydrochloric acid solution is 1 mol / L.
[0022] Furthermore, in step S2, the initiator is any one of ammonium persulfate, potassium persulfate or sodium persulfate.
[0023] Furthermore, in step I, the diameter of the sepiolite fiber is 1 to 5 μm and the length is 1 to 2 mm.
[0024] Furthermore, in step II, the mesh size of the sieving is 500 to 1000 meshes.
[0025] A production process for recycled daily-use ceramic products comprises the following steps:
[0026] Step 1: Prepare ceramic embryo
[0027] (1) collecting the waste ceramic products, then cleaning and classifying them, crushing the cleaned waste ceramic products using a double-roll mill, then adding the crushed ceramic products into a ball mill, ball-milling them to 100-300 meshes, and then performing magnetization to remove iron, to obtain waste ceramic product powder;
[0028] (2) adding the waste ceramic powder into a mixer, then adding deionized water, mixing and stirring for 5 to 8 hours to obtain a slurry;
[0029] (3) injecting the mixed slurry obtained in step (2) into a ceramic mold for molding, demolding to obtain a body, and then calcining the body at 950-1050° C. for 3-5 hours to obtain a ceramic body;
[0030] Step 2: Prepare glaze slurry
[0031] Add potassium feldspar, sodium feldspar, calcite, quartz, kaolin, silicon dioxide, aluminum oxide, calcium oxide, pigment, paraffin, inorganic antibacterial agent, inorganic modified additives in parts by weight into a container, stir evenly, then add deionized water for ball milling, pass through a 100-300 mesh sieve, and then perform vacuum degassing for 10-30 minutes to obtain a glaze slurry;
[0032] Step 3: Glaze the ceramic body
[0033] The glaze slurry obtained in step 2 is evenly coated on the surface of the ceramic body obtained in step 1 to obtain a glazed body;
[0034] Step 4: Firing and Cooling
[0035] The glazed body is calcined at 1200-1280°C for 5-7 hours, and a ceramic product is obtained after cooling.
[0036] Beneficial effects of the present invention:
[0037] (1) The present invention adopts an inorganic antibacterial agent as an antibacterial filler, which can effectively improve the antibacterial properties of ceramic products and prevent ceramic products from being contaminated by bacteria during use, thereby ensuring people's health and safety. In addition, the inorganic antibacterial agent is prepared from illite powder as a raw material, has porosity and a high specific area, so that copper ions and zinc ions are adsorbed on its surface or enter the pores, thereby being able to release copper ions and zinc ions, destroying the bacterial structure, improving the antibacterial properties of ceramic products, and achieving the purpose of sustained release, maintaining long-term antibacterial ability, and broadening the application range of ceramic products.
[0038] (2) The present invention utilizes electrostatic adsorption to combine sepiolite fiber with glass flake powder to prepare an inorganic modified additive. On the one hand, when the ceramic product is subjected to external force, the sepiolite fiber can disperse and transfer stress, thereby significantly improving the mechanical properties of the ceramic product. On the other hand, the glass flake powder has a fish scale effect, which can produce a barrier effect, extending the diffusion path of the corrosive medium in the ceramic product, making it tortuous and complex, thereby effectively improving the corrosion resistance of the ceramic product. In addition, the sepiolite fiber and the glass flake powder can form a special "ball" effect, which plays a role in reducing the friction coefficient, thereby improving the wear resistance of the ceramic product. The various raw materials each take advantage of their own strengths, give full play to and utilize their respective characteristics, and extend the service life of the ceramic product.
[0039] Of course, any product implementing the present invention does not necessarily need to achieve all of the advantages described above at the same time. BRIEF DESCRIPTION OF THE DRAWINGS
[0040] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the accompanying drawings required for describing the embodiments will be briefly introduced below. Obviously, the accompanying drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other accompanying drawings can be obtained based on these accompanying drawings without paying creative work.
[0041] Figure 1 This is a scanning electron microscope image of the sepiolite fiber and inorganic modified additive prepared in Example 1 of the present invention. DETAILED DESCRIPTION
[0042] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0043] Example 1
[0044] 1. Preparation of Inorganic Antibacterial Agents
[0045] S1: adding 5 g of illite powder with a particle size of 4 μm into a hydrochloric acid solution with a volume fraction of 20%, stirring at 60° C. for 2 h, and then filtering, washing, and vacuum drying to obtain pretreated illite powder;
[0046] S2: Dissolve 3 ml aniline in a hydrochloric acid solution with a concentration of 1 mol / L, add 3 g pretreated illite powder, disperse by ultrasonic for 1.5 h, then add 0.2 g potassium persulfate, stir and mix evenly, react in an ice bath at 2 ° C for 8 h, filter, wash and dry to obtain modified illite powder;
[0047] S3: Add 10 g of modified illite powder into deionized water, and disperse it by ultrasonic for 1.5 h. Then add 2.1 g of zinc chloride and 1.2 g of copper nitrate, and continue to stir and mix for 9 h. Then filter and dry to obtain an inorganic antibacterial agent.
[0048] 2. Preparation of Inorganic Modified Additives
[0049] Ⅰ: 10 g of sepiolite fiber with a diameter of 4 μm and a length of 2 mm was added to 90% ethanol by volume, and ultrasonically dispersed for 30 min, and then 0.53 g of trimethyl [3- (trimethoxysilyl) propyl] ammonium chloride was added, stirred and mixed, and reacted at 50° C. for 3 h. After the reaction was completed, the solid material was filtered out, washed, and dried to obtain modified sepiolite fiber;
[0050] Ⅱ: Place 5g of modified sepiolite fiber in deionized water, ultrasonically disperse for 30 minutes, add 4.5g of glass flake powder, ultrasonically disperse for 1.5 hours, let stand for 1.5 hours, then filter, vacuum dry, collect the product, grind through an 800-mesh sieve, and obtain an inorganic modified additive.
[0051] The morphology of sepiolite fibers and inorganic modified additives was analyzed using a Quanta 250FEG scanning electron microscope. The test results are shown in Figure 1 , where A is sepiolite fiber and B is inorganic modified additive. Figure 1 It can be seen that the sepiolite fiber has a straight rod-shaped fiber structure with a smooth surface, and the surface of the inorganic modified additive obviously presents an uneven surface morphology. This is because the negatively charged glass flake powder is attached to the surface of the sepiolite fiber through electrostatic adsorption, so the inorganic modified additive presents an uneven surface morphology.
[0052] 3. Preparation of ceramic products
[0053] Step 1: Prepare ceramic embryo
[0054] (1) collecting the waste ceramic products, then cleaning and classifying them, crushing the cleaned waste ceramic products using a double-roll mill, then adding the crushed ceramic products into a ball mill, ball-milling them to 100 mesh, and then performing magnetization to remove iron, to obtain waste ceramic product powder;
[0055] (2) adding the waste ceramic powder into a mixer, then adding deionized water, mixing and stirring for 5 hours to obtain a slurry;
[0056] (3) injecting the mixed slurry obtained in step (2) into a ceramic mold for molding, demolding to obtain a body, and then calcining the body at 950° C. for 3 h to obtain a ceramic body;
[0057] Step 2: Prepare glaze slurry
[0058] Add 10 g potassium feldspar, 7 g sodium feldspar, 6 g calcite, 1.5 g quartz, 0.5 g kaolin, 2.5 g silicon dioxide, 2.5 g aluminum oxide, 2 g calcium oxide, 1.5 g laterite, 1.5 g paraffin, 2.5 g inorganic antibacterial agent, and 2 g inorganic modified additive into a container, stir evenly, then add 30 g deionized water for ball milling, pass through a 100 mesh sieve, and then perform vacuum degassing for 10 minutes to obtain a glaze slurry;
[0059] Step 3: Glaze the ceramic body
[0060] The glaze slurry obtained in step 2 is evenly coated on the surface of the ceramic body obtained in step 1 to obtain a glazed body;
[0061] Step 4: Firing and Cooling
[0062] The glazed body is calcined at 1200°C for 5 hours and then cooled to obtain a ceramic product.
[0063] Example 2
[0064] Preparation of ceramic products
[0065] Step 1: Prepare ceramic embryo
[0066] (1) collecting the waste ceramic products, then cleaning and classifying them, crushing the cleaned waste ceramic products using a double-roll mill, then adding the crushed ceramic products into a ball mill, ball-milling them to 200 mesh, and then performing magnetization to remove iron, to obtain waste ceramic product powder;
[0067] (2) adding the waste ceramic powder into a mixer, then adding deionized water, mixing and stirring for 7 hours to obtain a slurry;
[0068] (3) injecting the mixed slurry obtained in step (2) into a ceramic mold for molding, demolding to obtain a embryo body, and then calcining the embryo body at 1000° C. for 4 hours to obtain a ceramic embryo body;
[0069] Step 2: Prepare glaze slurry
[0070] Add 13 g potassium feldspar, 10 g sodium feldspar, 8 g calcite, 2 g quartz, 1 g kaolin, 3.5 g silicon dioxide, 3.5 g aluminum oxide, 2.5 g calcium oxide, 2 g laterite, 2 g paraffin, 3.5 g inorganic antibacterial agent, and 3 g inorganic modified additive into a container, stir evenly, then add 40 g deionized water for ball milling, pass through a 200 mesh sieve, and then perform vacuum degassing for 20 minutes to obtain a glaze slurry;
[0071] Step 3: Glaze the ceramic body
[0072] The glaze slurry obtained in step 2 is evenly coated on the surface of the ceramic body obtained in step 1 to obtain a glazed body;
[0073] Step 4: Firing and Cooling
[0074] The glazed body is calcined at 1240°C for 6 hours and then cooled to obtain a ceramic product.
[0075] The preparation method of the inorganic antibacterial agent and the inorganic modified additive is the same as that in Example 1.
[0076] Example 3
[0077] Preparation of ceramic products
[0078] Step 1: Prepare ceramic embryo
[0079] (1) collecting the waste ceramic products, then cleaning and classifying them, crushing the cleaned waste ceramic products using a double-roll mill, then adding the crushed ceramic products into a ball mill, ball-milling them to 300 mesh, and then performing magnetization to remove iron, to obtain waste ceramic product powder;
[0080] (2) adding the waste ceramic powder into a mixer, then adding deionized water, mixing and stirring for 8 hours to obtain a slurry;
[0081] (3) injecting the mixed slurry obtained in step (2) into a ceramic mold for molding, demolding to obtain an embryo body, and then calcining the embryo body at 1050° C. for 5 hours to obtain a ceramic embryo body;
[0082] Step 2: Prepare glaze slurry
[0083] Add 15g potassium feldspar, 12g sodium feldspar, 9g calcite, 2.5g quartz, 1.5g kaolin, 5g silicon dioxide, 4g aluminum oxide, 3g calcium oxide, 2.5g laterite, 2.5g paraffin, 5g inorganic antibacterial agent, and 4g inorganic modified additive into a container, stir evenly, then add 50g deionized water for ball milling, pass through a 300 mesh sieve, and then perform vacuum degassing for 30 minutes to obtain a glaze slurry;
[0084] Step 3: Glaze the ceramic body
[0085] The glaze slurry obtained in step 2 is evenly coated on the surface of the ceramic body obtained in step 1 to obtain a glazed body;
[0086] Step 4: Firing and Cooling
[0087] The glazed body is calcined at 1280°C for 7 hours and a ceramic product is obtained after cooling.
[0088] The preparation method of the inorganic antibacterial agent and the inorganic modified additive is the same as that in Example 1.
[0089] Comparative Example 1
[0090] Preparation of ceramic products
[0091] Step 1: Prepare ceramic embryo
[0092] (1) collecting the waste ceramic products, then cleaning and classifying them, crushing the cleaned waste ceramic products using a double-roll mill, then adding the crushed ceramic products into a ball mill, ball-milling them to 200 mesh, and then performing magnetization to remove iron, to obtain waste ceramic product powder;
[0093] (2) adding the waste ceramic powder into a mixer, then adding deionized water, mixing and stirring for 7 hours to obtain a slurry;
[0094] (3) injecting the mixed slurry obtained in step (2) into a ceramic mold for molding, demolding to obtain a embryo body, and then calcining the embryo body at 1000° C. for 4 hours to obtain a ceramic embryo body;
[0095] Step 2: Prepare glaze slurry
[0096] Add 13 g potassium feldspar, 10 g sodium feldspar, 8 g calcite, 2 g quartz, 1 g kaolin, 3.5 g silicon dioxide, 3.5 g aluminum oxide, 2.5 g calcium oxide, 2 g laterite, 2 g paraffin, and 3.5 g inorganic antibacterial agent into a container, stir evenly, then add 40 g deionized water for ball milling, pass through a 200 mesh sieve, and then perform vacuum degassing for 20 minutes to obtain a glaze slurry;
[0097] Step 3: Glaze the ceramic body
[0098] The glaze slurry obtained in step 2 is evenly coated on the surface of the ceramic body obtained in step 1 to obtain a glazed body;
[0099] Step 4: Firing and Cooling
[0100] The glazed body is calcined at 1240°C for 6 hours and then cooled to obtain a ceramic product.
[0101] The preparation method of the inorganic modified additive is the same as that in Example 1.
[0102] Comparative Example 2
[0103] Preparation of ceramic products
[0104] Step 1: Prepare ceramic embryo
[0105] (1) collecting the waste ceramic products, then cleaning and classifying them, crushing the cleaned waste ceramic products using a double-roll mill, then adding the crushed ceramic products into a ball mill, ball-milling them to 200 mesh, and then performing magnetization to remove iron, to obtain waste ceramic product powder;
[0106] (2) adding the waste ceramic powder into a mixer, then adding deionized water, mixing and stirring for 7 hours to obtain a slurry;
[0107] (3) injecting the mixed slurry obtained in step (2) into a ceramic mold for molding, demolding to obtain a embryo body, and then calcining the embryo body at 1000° C. for 4 hours to obtain a ceramic embryo body;
[0108] Step 2: Prepare glaze slurry
[0109] Add 13 g of potassium feldspar, 10 g of sodium feldspar, 8 g of calcite, 2 g of quartz, 1 g of kaolin, 3.5 g of silicon dioxide, 3.5 g of aluminum oxide, 2.5 g of calcium oxide, 2 g of laterite, 2 g of paraffin wax, and 3 g of inorganic modified additives into a container, stir evenly, then add 40 g of deionized water for ball milling, pass through a 200 mesh sieve, and then perform vacuum degassing for 20 minutes to obtain a glaze slurry;
[0110] Step 3: Glaze the ceramic body
[0111] The glaze slurry obtained in step 2 is evenly coated on the surface of the ceramic body obtained in step 1 to obtain a glazed body;
[0112] Step 4: Firing and Cooling
[0113] The glazed body is calcined at 1240°C for 6 hours and then cooled to obtain a ceramic product.
[0114] The preparation method of the inorganic modified additive is the same as that in Example 1.
[0115] Comparative Example 3
[0116] Preparation of ceramic products
[0117] Step 1: Prepare ceramic embryo
[0118] (1) collecting the waste ceramic products, then cleaning and classifying them, crushing the cleaned waste ceramic products using a double-roll mill, then adding the crushed ceramic products into a ball mill, ball-milling them to 200 mesh, and then performing magnetization to remove iron, to obtain waste ceramic product powder;
[0119] (2) adding the waste ceramic powder into a mixer, then adding deionized water, mixing and stirring for 7 hours to obtain a slurry;
[0120] (3) injecting the slurry obtained in step (2) into a ceramic mold for molding, demolding to obtain a body, and then calcining the body at 1000° C. for 4 hours to obtain a ceramic body;
[0121] Step 2: Prepare glaze slurry
[0122] Add 13 g potassium feldspar, 10 g sodium feldspar, 8 g calcite, 2 g quartz, 1 g kaolin, 3.5 g silicon dioxide, 3.5 g aluminum oxide, 2.5 g calcium oxide, 2 g laterite, and 2 g paraffin into a container, stir evenly, then add 40 g deionized water for ball milling, pass through a 200 mesh sieve, and then perform vacuum degassing for 20 minutes to obtain a glaze slurry;
[0123] Step 3: Glaze the ceramic body
[0124] The glaze slurry obtained in step 2 is evenly coated on the surface of the ceramic body obtained in step 1 to obtain a glazed body;
[0125] Step 4: Firing and Cooling
[0126] The glazed body is calcined at 1240°C for 6 hours and then cooled to obtain a ceramic product.
[0127] Performance Testing
[0128] ① According to JC / T 897-2014 "Antibacterial Performance of Antibacterial Ceramic Products", the antibacterial performance of the ceramic products prepared in Examples 1 to 3 and Comparative Examples 1 to 3 was tested, and the test bacteria were Escherichia coli and Staphylococcus aureus. The test results are as follows:
[0129]
[0130] From the test results in the above table, it can be seen that the initial antibacterial rate and the antibacterial rate after 5 days of the ceramic products prepared in Examples 1 to 3 and Comparative Example 1 against Escherichia coli and Staphylococcus aureus can be maintained above 90%, so they have excellent antibacterial effects and can achieve continuous antibacterial effects; No inorganic antibacterial agent was added to the ceramic products prepared in Comparative Examples 2 and 3, and the initial antibacterial rate and the antibacterial rate after 5 days against Escherichia coli and Staphylococcus aureus were both below 80%, and the antibacterial effect was poor.
[0131] ② The ceramic products prepared in Examples 1 to 3 and Comparative Examples 1 to 3 were electrochemically tested in simulated body fluid using an electrochemical workstation, the non-working surface was sealed with nail polish, and the corrosion resistance test was performed at room temperature; the ceramic products prepared in Examples 1 to 3 and Comparative Examples 1 to 3 were tested for impact strength according to GB / T38494-2020 “Ceramic Impact Test Method”; the ceramic products prepared in Examples 1 to 3 and Comparative Examples 1 to 3 were tested for wear resistance according to GB / T 3810.7-2016 “Ceramic Tile Test Method Part 7: Determination of Surface Wear Resistance of Glazed Tile”, and the test results are as follows:
[0132]
[0133] From the test results in the above table, it can be seen that the self-corrosion current density of the ceramic products prepared in Examples 1 to 3 and Comparative Example 2 is relatively small, and the impact strength is greater than 3J / cm 2 , the wear resistance is graded as level 4, so it has good corrosion resistance, mechanical properties and wear resistance; In the ceramic product prepared in comparative example 1, an inorganic antibacterial agent is added, but no inorganic modified additive is added, the self-corrosion current density is large, and the impact strength is less than 1.5 J / cm 2, the wear resistance is graded into four levels. Compared with the examples, the corrosion resistance and mechanical properties of the ceramic products are poor, but the wear resistance is good. In the ceramic products prepared in comparative example 3, neither inorganic antibacterial agents nor inorganic modified additives are added, so the corrosion resistance, mechanical properties and wear resistance of the prepared ceramic products are poor.
[0134] The above contents are merely examples and explanations of the concept of the present invention. The technicians in this technical field may make various modifications or additions to the specific embodiments described or replace them in a similar manner. As long as they do not deviate from the concept of the invention or exceed the scope defined by the claims, they should all fall within the protection scope of the present invention.
Claims
1. A recycled daily-use ceramic product, characterized in that: The invention is composed of a ceramic body and a glaze slurry coated on the surface of the ceramic body; the ceramic body is made of waste ceramic products after processing; the glaze slurry comprises the following raw materials by weight: 20 to 30 parts of potassium feldspar, 15 to 25 parts of sodium feldspar, 12 to 18 parts of calcite, 3 to 5 parts of quartz, 1 to 3 parts of kaolin, 5 to 10 parts of silicon dioxide, 5 to 8 parts of aluminum oxide, 4 to 6 parts of calcium oxide, 3 to 5 parts of pigment, 3 to 5 parts of paraffin wax, 5 to 10 parts of inorganic antibacterial agent, 4 to 8 parts of inorganic modified additive, and 60 to 100 parts of deionized water; the inorganic antibacterial agent is to adsorb copper ions and zinc ions on illite powder; the inorganic modified additive is to combine sepiolite fiber with glass flake powder through electrostatic adsorption; The preparation method of the inorganic antibacterial agent comprises the following steps: S1: adding illite powder to a hydrochloric acid solution, stirring at 50-70° C. for 1-3 hours, and then filtering, washing, and vacuum drying to obtain pretreated illite powder; S2: dissolving aniline in hydrochloric acid solution, adding pretreated illite powder, ultrasonically dispersing for 1-2 hours, then adding initiator, stirring and mixing evenly, reacting in an ice bath at 0-4°C for 6-10 hours, filtering, washing and drying to obtain modified illite powder; S3: adding the modified illite powder to deionized water, ultrasonically dispersing for 1 to 2 hours, then adding zinc chloride and copper nitrate, continuing to stir and mix for 8 to 10 hours, then filtering and drying to obtain an inorganic antibacterial agent; The preparation method of the inorganic modified additive comprises the following steps: Ⅰ: Add sepiolite fiber to ethanol, ultrasonically disperse for 20 to 40 minutes, then add trimethyl [3- (trimethoxysilyl) propyl] ammonium chloride, stir and mix, react at 40 to 60 ° C for 2 to 4 hours, and after the reaction is completed, filter out the solid material, wash and dry to obtain modified sepiolite fiber; II: Place the modified sepiolite fiber in deionized water, ultrasonically disperse it for 20 to 40 minutes, add glass flake powder, ultrasonically disperse it for 1 to 2 hours, let it stand for 1 to 2 hours, then filter, vacuum dry, collect the product, grind and sieve it to obtain an inorganic modified additive.
2. A recycled daily-use ceramic product according to claim 1, characterized in that: The pigment is any one of cinnabar, red clay or malachite green.
3. A recycled daily-use ceramic product according to claim 1, characterized in that: In step S1, the particle size of the illite powder is 1 to 10 μm.
4. The recycled daily-use ceramic product according to claim 1, characterized in that: In step S2, the concentration of the hydrochloric acid solution is 1 mol / L.
5. The recycled daily-use ceramic product according to claim 1, characterized in that: In step S2, the initiator is any one of ammonium persulfate, potassium persulfate or sodium persulfate.
6. The recycled daily-use ceramic product according to claim 1, characterized in that: In step I, the diameter of the sepiolite fiber is 1 to 5 μm and the length is 1 to 2 mm.
7. The recycled daily-use ceramic product according to claim 1, characterized in that: In step II, the mesh size of the sieving is 500 to 1000 meshes.
8. The production process of recycled daily-use ceramic products as claimed in claim 1, characterized in that: The production process comprises the following steps: Step 1: Preparation of ceramic body (1) collecting the waste ceramic products, then cleaning and classifying them, crushing the cleaned waste ceramic products using a double-roll mill, then adding the crushed ceramic products into a ball mill, ball-milling them to 100-300 meshes, and then performing magnetization to remove iron, to obtain waste ceramic product powder; (2) adding the waste ceramic powder into a mixer, then adding deionized water, mixing and stirring for 5 to 8 hours to obtain a slurry; (3) injecting the slurry obtained in step (2) into a ceramic mold for molding, demolding to obtain a green body, and then calcining the green body at 950 to 1050° C. for 3 to 5 hours to obtain a ceramic green body; Step 2: Prepare glaze slurry Add potassium feldspar, sodium feldspar, calcite, quartz, kaolin, silicon dioxide, aluminum oxide, calcium oxide, pigment, paraffin, inorganic antibacterial agent, inorganic modified additives in parts by weight into a container, stir evenly, then add deionized water for ball milling, pass through a 100-300 mesh sieve, and then perform vacuum degassing for 10-30 minutes to obtain a glaze slurry; Step 3: Glazing the ceramic body The glaze slurry obtained in step 2 is evenly coated on the surface of the ceramic body obtained in step 1 to obtain a glazed body; Step 4: Firing and Cooling The glazed body is calcined at 1200-1280°C for 5-7 hours, and a ceramic product is obtained after cooling.
Citation Information
Patent Citations
Antibacterial sanitary ceramic and preparation method thereof
CN103482957B
Cation modified clay
GB665474A
Liquid curable composition
KR1020130048748A
Cited By
Domestic ceramic product and preparation method thereof
CN121929993A